Cattle theft, criminal action and non-state justice: the birth of public penal action conditionate to representation in Brazil (1860-1899) - Lucas Ribeiro Garro (Revista Brasileira de Direito Processual Penal)
The present work seeks to answer the question: how the birth of public penal action conditionate to representation in Brazil, was related to non-institutionalized justice practices connected with the cattle theft. To achieve this goal, we will analyze the birth of the penal action conditioned to the representation and its relation with the crime of cattle theft, between 1860, year of birth of this crime, and 1899, when this penal action was no more applied to the cattle theft crime. This examination will be based on national and international legal context, through a historical-comparative perspective, contextualizing the discourses about this action and the crime of cattle theft in the scope of its national and international interlocutors. In order to do so, we used methodological tools based on the comparative history of law, such as the international insertion of the study object to understand the possible relation between the conditioned public criminal action and the practices of negotiation between the parties. From these perspectives, we analyzed parliamentary debates, national and international doctrines on criminal action. Until now were discovered that the search for the “publicization” of criminal justice in Brazil was marked by negotiations in a way that the non-state justice was not eliminate but absorbed and overlaid by the state justice.